Effect of the Cation on the Interactions between Alkyl Methyl Imidazolium Chloride Ionic Liquids and Water - Khan, Imran
A systematic study of the interactions between water and alkyl methyl imidazolium chloride ionic liquids at 298.2 K, based on activity coefficients estimated from water activity measurements in the entire solubility range, is presented. The results show that the activity coefficients of water in the studied ILs are controlled by the hydrophilicity of the cation and the cation-anion interaction. To achieve a deeper understanding on the interactions between water and the ILs, COSMO-RS and FTIR spectroscopy were also applied. COSMO-RS was used to predict the activity coefficient of water in the studied ionic liquids along with the excess enthalpies, suggesting the formation of complexes between three molecules of water and one IL molecule. On the basis of quantum-chemical calculations, it is found that cation-anion interaction plays an important role upon the ability of the IL anion to interact with water. The changes in the peak positions/band areas of OH vibrational modes of water as a function of IL concentration were investigated, and the impact of the cation on the hydrogen-bonding network of water is identified and discussed.